Monetary Expenses of Families of Workers and Engineers of Industrial Enterprises in Sverdlovsk Region in the First Five Post-War Years (1946-1950) - V. N. Mamyachenkov (Научный диалог)
The article is devoted to the subject insufficiently developed in the national historiography both in federal and regional aspects. The purpose of writing this work was to study monetary expenses of the most numerous groups of the population of the USSR - families of workers and technical workers (engineers) of industrial enterprises. It is declared that the level of expenditure is the determining factor in the standard of living of all categories of citizens. It is argued that today it is impossible to say that the family budgets of workers and engineers of industrial enterprises are well-developed by social scientists: historians, sociologists and economists. It is emphasized that the author of the proposed article has repeatedly appealed to the development of family budgets of industrial workers and engineers. It is stated that the documentary base of the article was primarily the materials of budget surveys of families of industrial workers and engineers, stored in the funds of the state archive of the Sverdlovsk region. It is proved that the housing conditions of engineer families were much better than of the families of workers and employees of industrial enterprises. It is stated that the cost of food in absolute terms remained almost the same in the surveyed families throughout the study period. It is concluded that the average per capita cash expenditure of engineer families was higher than that of workers’ families.